The associations between injury mechanism and extended hospital stay among pediatric patients: findings from a trauma Center in Saudi Arabia - Suliman Alghnam; Jawaher Ali Towhari; Ibrahim Al Babtain; Muhannad Al Nahdi; Mohammed Hamad Aldebasi; Mahna Alyami; Hamad Alkhalaf (BMC, 2019)
Abstract Background A hospitalized patient's length of stay (LOS) can have a significant impact on the performance and operating costs of a healthcare facility. Among pediatric patients, traumatic injuries are common causes of emergency room visits and hospitalizations. In Saudi Arabia, little is known about the burden of pediatric traumas on population health and the healthcare facilities. Therefore, the aim of this study was to investigate the associations between traumatic pediatric injury mechanisms and extended LOS in a trauma center. Methods Data was obtained from the trauma registry. From 2001 to 2018, trauma patients between the ages of 0 and 18 years old with LOSs of > 0 days were analyzed. The independent variable was the injury mechanism, which was classified as follows: falls, burns, drowning, motor vehicle collisions, motorcycle collisions, pedestrian, and intentional injuries. The dependent variable was an extended LOS defined as ≥21 days. A multivariate logistic regression analysis was used to evaluate the associations between the injury mechanisms and an extended LOS. Results A total of 5563 pediatric patients were included in this study. Of those, 774 (14%) had extended LOSs. Those patients with extended LOSs suffered more severe injuries than those with short hospital stays as measured by the Injury Severity Score (mean scores: 15.4 vs. 6.8, p < 0.01), the Glasgow Coma Scale score (mean scores: 10.4 vs, 14.0, p < 0.01), and the Revised Trauma Score (mean scores: 9.9 vs. 11.0, p < 0.01). Approximately one half of the patients with extended LOSs were admitted due to motor vehicle injuries. In addition, those patients were almost five times more likely to have extended LOSs than the patients who suffered fall injuries (odds ratio: 4.8, 95% confidence interval: 3.2-7.1). Conclusions Based on the study results, motor vehicle injuries were significantly associated with extended hospitalizations. Prevention is instrumental for reducing healthcare utilization; therefore, these findings call for public health professionals and policymakers to plan, design, and implement preventive measures to reduce the traffic injury burden. In addition, increased traffic law enforcement, such as the use of car restraints, is warranted to reduce the preventable injuries and improve the overall population health.